2017
DOI: 10.1016/j.tics.2017.03.008
|View full text |Cite|
|
Sign up to set email alerts
|

Neural Noise Hypothesis of Developmental Dyslexia

Abstract: Developmental dyslexia (decoding-based reading disorder; RD) is a complex trait with multifactorial origins at the genetic, neural and cognitive levels. There is evidence that low-level sensory processing deficits precede and underlie phonological problems, which are one of the best-documented aspects of RD. RD is also associated with impairments in integrating visual symbols with their corresponding speech sounds. Although causal relationships between sensory processing, print-speech integration and fluent re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
124
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(138 citation statements)
references
References 115 publications
13
124
0
1
Order By: Relevance
“…The neural noise hypothesis 769 for RD has a wide range of implications in sensory processing, representation formation, and 770 multisensory integration across the auditory and visual domains. Of relevance to our current 771 findings, Hancock et al (2017) propose that neural noise in the auditory domain may affect the 772 time window for sensory processing and integration that is crucial for learning speech and non-773 speech sound categories (e.g., Gabay & Holt, 2015;Vandermosten et al, 2010). 774…”
Section: Representations 765mentioning
confidence: 75%
See 1 more Smart Citation
“…The neural noise hypothesis 769 for RD has a wide range of implications in sensory processing, representation formation, and 770 multisensory integration across the auditory and visual domains. Of relevance to our current 771 findings, Hancock et al (2017) propose that neural noise in the auditory domain may affect the 772 time window for sensory processing and integration that is crucial for learning speech and non-773 speech sound categories (e.g., Gabay & Holt, 2015;Vandermosten et al, 2010). 774…”
Section: Representations 765mentioning
confidence: 75%
“…In a recent review, Hancock, Pugh, and Hoeft (2017) propose a neural noise hypothesis 766 and postulate that increased neural noise (i.e., stochastic variability in neural response) results 767 from higher cortical excitability due to imbalance in specific neurochemistry (e.g., glutamate; 768 Pugh et al, 2014), which then leads to atypical neural oscillations. The neural noise hypothesis 769 for RD has a wide range of implications in sensory processing, representation formation, and 770 multisensory integration across the auditory and visual domains.…”
Section: Representations 765mentioning
confidence: 99%
“…() discovered that a polymorphism of DCDC2 revealed differences in cortical morphology of healthy individuals. Based upon results from DCDC2 animal models, which show impaired rapid auditory processing similar to the deficits found in children at risk for RD, Hancock and associates () advance a “neural noise” hypothesis in which RD risk genes (i.e., DCDC2 and KIAA0319 ) affect two pathways—enhanced glutamatergic signaling and disrupted neural migration—to increase noise. They suggest that possibly each pathway increases neural noise through inducing neural hyperexcitability, shifting the normal cortical excitation–inhibition balance.…”
Section: Reading At Two Levels: As the Biological System And As The Mmentioning
confidence: 97%
“…However, a 2007 review reported that no specific cognitive processes are known to be influenced by the proposed genes (Schumacher, Hoffmann, Schmäl, Schulte‐Körne, & Nöthen, ). In such a controversial context, it is interesting to note that, according to Hancock, Pugh, and Hoeft (), several genetic risk variants have been associated with RD, with an average allele frequency of .28 in a U.S. RD population; in a German population, short DCDC2 deletions were found in 18% of RD individuals versus 9% of controls.…”
Section: Reading At Two Levels: As the Biological System And As The Mmentioning
confidence: 99%
“…Currently little is known regarding either normal or atypical development of this oscillatory hierarchy, although there is clear evidence for maturational changes (Cho et al, ). Future studies of RD—using the approaches we have discussed here—at the level of neural oscillations, in conjunction with measures of neurometabolite concentrations (e.g., Pugh et al, ) and growing understanding of the spatial and temporal characteristics of gene expression in the human brain (Kang et al, ) may be highly informative for understanding the etiology of RD at a more detailed biological level (Hancock, Pugh, & Hoeft, in press).…”
Section: Future Directionsmentioning
confidence: 99%